2007
DOI: 10.1093/ndt/gfm452
|View full text |Cite
|
Sign up to set email alerts
|

Exit of catheter lock solutions from double lumen acute haemodialysis catheters an in vitro study

Abstract: All double lumen dialysis catheters we tested have a substantial amount of leak even when the catheter 'lock' volumes were used, and leak ratio increases significantly with 20% overfill. There is a leak even when using 20% less 'lock' volume. The amount of leak can be clinically important and may explain the reports of bleeding episodes after heparin lock and antibiotic toxicity after antibiotic and anticoagulant combination lock. Some devices have lower leak ratios than others, likely related to catheter desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 9 publications
2
49
0
2
Order By: Relevance
“…No catheter seems to be free of this problem. An in vitro study of five different double lumen catheters showed that systemic leakage was greatest with 20% overfill (34).…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…No catheter seems to be free of this problem. An in vitro study of five different double lumen catheters showed that systemic leakage was greatest with 20% overfill (34).…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…However, a major complication of heparin locks, especially in the perioperative period, is bleeding due to unsuspected anticoagulation [58]. This is the result of leakage of lock solution from the catheter due to parabolic flow patterns in the catheter [59,60]. Trisodium citrate (30%) is an intraluminal locking agent that has been shown to significantly reduce the rate of CRB [61].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
“…An aliquot of the catheter solution invariably leaks into the systemic circulation (3,4). As a result, higher heparin lock concentrations have the potential to cause systemic bleeding caused by inadvertent systemic anticoagulation (5,6). A recent study reported a higher frequency of hemorrhagic complications after placement of a new dialysis catheter in patients receiving a high-concentration heparin lock (7).…”
mentioning
confidence: 99%